Ancient mitochondrial DNA reveals convergent evolution of giant short-faced bears (Tremarctinae) in North and South America - Mitchell, Kieren J.; Bray, Sarah C.; Bover, Pere; Soibelzon, Leopoldo; Schubert, Blaine W.; Prevosti, Francisco; Prieto, Alfredo; Martin, Fabiana Maria; Austin, Jeremy J.; Cooper, Alan (My University, 2016)
The Tremarctinae are a subfamily of bears endemic to the New World, including two of the largest terrestrial mammalian carnivores that have ever lived: the giant, short-faced bears Arctodus simus from North America and Arctotherium angustidens from South America (greater than or equal to 1000 kg). Arctotherium angustidens became extinct during the Early Pleistocene, whereas Arctodus simus went extinct at the very end of the Pleistocene. The only living tremarctine is the spectacled bear (Tremarctos ornatus), a largely herbivorous bear that is today only found in South America. The relationships among the spectacled bears (Tremarctos), South American short-faced bears (Arctotherium) and North American short faced bears (Arctodus) remain uncertain. In this study, we sequenced a mitochondrial genome from an Arctotherium femur preserved in a Chilean cave. Our molecular phylogenetic analyses revealed that the South American short-faced bears were more closely related to the extant South American spectacled bear than to the North American short-faced bears. This result suggests striking convergent evolution of giant forms in the two groups of short-faced bears (Arctodus and Arctotherium), potentially as an adaptation to dominate competition for megafaunal carcasses.
Keywords: ursidae; great american biotic interchange; molecular dating; palaeontology